Beneški bienale sodobne umetnosti in pouk likovne umetnosti v osnovni šoli - Zupančič, Tomaž; Velikonja, Andrej (Revija za elementarno izobraževanje, 2017)
The Venice Biennale of Contemporary Art and Arts in Basic School. The paper presents an empirical study on introducing contemporary art into teaching practice. The introduction emphasises the importance of contemporary art and provides a chronological overview of the last fifteen years of the Venice Biennale and didactic guidelines on introducing contemporary art into the classroom. The empirical part presents a qualitative study that was conducted in 2015/16 using a sample of 117 students of the last triennium of basic school. The selected works were used to prepare three thematic units. The students’ response has shown multiple positive aspects. The differences in students’ response with regard to age have been emphasised. Guidelines for implementing art education classes on the basis of contemporary art practices have been prepared.
Keywords: contemporary art; art education; visual art; basic school; Venice Biennale